MORPHOFUNCTIONAL FEATURES OF THE DEVELOPMENT OF SCHOOL-AGE CHILDREN LIVING IN CONDITIONS OF HIGH MOUNTAINS - Isayev, I.I.; Агаєв М. А. (World of Medicine and Biology, 2015)
The 345 school children from Lerik (Azerbaijan) aged from 6-17 years were surveyed for the purpose of health, nutrition, physical development, harmony and the morpho-functional features of development of children living in conditions of high mountains. Various chronic diseases were detected in 8.40% (29) children. The first group consisted of 61.45% (212) children, a second group of 30,15 % (104) children. Along with increased age, we observed the relative superiority of boys and susceptibility to changes in the low group health and nutrition index that do not comply with the age. Among young school-age children we revealed : average physical level in 60,38 % cases; below average 16,98%, low 8,49 %; above average 10,38% and 3,77% high level. The average level of middle age schoolchildren is decreased and amounted to 13, 27 %. Among senior school-age children : average physical level in 22,32 % cases; below average 25,89%, low 11,61 %; above average 31,25% and 8,93% high level. The growth sprut in boys is, on average, about 2 years later than that of girls (12-13 for boys and 11 for girls) in normal. But in children living in conditions of high mountains growth sprut in boys was in 15 and in girls 14-15 years. Dynamic increase of weight of a body and growth is late and proceeds slowly. All this leads to infringement of individual progress. The mutual disharmony growing with age antrometric indicators have been diagnosed in 40.51% of the children. We remarked that disharmony among boys was particularly high. The disharmony in 36.39% cases was distributed generally and gender 36.63% and 36.11%. Boy’s acute disharmony (4.12%) compared to girls (2.78%) was twice more. Thus long and stable delay of body growth and weight in the pre puberty and puberty period can be measured as an indicator of the presence in the body chronic stress.